Reporte de caso clínico de absceso en un gato. Informe pasantía en la clínica veterinaria Abanimal imágenes diagnósticas (2022)
The internship is an excellent opportunity to put into practice all the both theoretical and practical knowledge acquired during the professional career. The Abanimal veterinary clinic is a leader in the area of ​​diagnostic images worldwide. national, dedicated to the care of companion pets such as dogs and cats. This entity offers the possibility of carrying out the internship within its facilities and On this occasion, the practices were carried out in the areas of ultrasound and the hospital, during the internship period the objective of the clinic is to train a professional with integrity and capable of making decisions in the face of the different cases that arise present in internal medicine and thus prepare it for the professional challenges of veterinary medicine in small animals. The areas of performance during this internship was the hospital area in which basic care and specialized for each patient, also in the ultrasound area which has advanced equipment and high quality standards. At the end of the process, the intern must Make a report of a clinical case of interest that you have seen during your entire layoff. The case of a cat with an abscess is exposed, since they are infectious processes important that frequently occurs in outdoor cats